Application of Web-based Learning Material for Teaching States of Matter in 8th Grade Primary School Chemistry – A Pilot Study Results - Nuić, Ines; Glažar, Saša Aleksej (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2015)
This paper presents results of a pilot study that investigated the progression in primary school students' conceptions of the structure and states of matter while learning with a new instructional approach dealing with these concepts. The study begun in May and was continued in September 2013. In the first part of the study we included 108 7th grade students (aged 12-13) from two primary schools, and in the second part we continued the study with 57 8th grade students (aged 13-14) from one school. Web-based learning material was applied as instructional tool during teaching of Structure of matter and States of matter, containing both macro and sub-micro level of representation. Students were asked to fulfill tests of knowledge dealing with macroscopic and submicroscopic level of representation. Results showed better understanding of structure and states of matter but also some persistent misconceptions that could be addressed in the following period.